Enhancing the Capabilities of Church-based Family Planning Counsellors with the Billings Ovulation Method - Lorensia Panselina Widowati; Baharika Suci Dwi Aningsih; Dewi Novitasari Suhaid; Dyah Woro Kartiko Kusumo Wardani; Ni Nyoman Sri Artina Dewi; Frenta Helena Simaibang; Yosefin Beni Purbo Utami; Kusuma Dini (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
A strategy to enhance the welfare of families is family planning. Couples are given the freedom to decide what is best for their family when it comes to the number of children and the spacing between births. An autonomous, simple, affordable, and Catholic-compliant method of contraception is natural family planning with the Billings ovulation method. For the purpose to complete this community service project, representatives from Catholic churches are trained about the Billings ovulation method. Participants in this activity acquire information and guidance on how to observe cervical mucus. In order to address any circumstances that may arise during observations, participants are also instructed. It is intended that after completing this course, the participants will be qualified to become counsellors in their own settings.